Analysis of Soil by Magnetic Field Assisted Calibration-Free Laser Induced Breakdown Spectroscopy (CF-LIBS) and Laser Ablation – Time-of-Flight Mass Spectrometry (LA-TOF-MS). (22nd September 2019) - Akhtar, Mahmood; Jabbar, Abdul; Mahmood, Shaukat; Umar, Zeshan Adeel; Ahmed, Rizwan; Aslam Baig, Muhammad
Abstract: The qualitative and quantitative analysis of soil samples collected from Sialkot, Pakistan (which contains leather industrial plants), has been performed using laser-induced breakdown spectroscopy (LIBS) and laser ablation time of flight mass spectrometry (LA-TOF-MS). The focused beam of a Q-switched Nd: YAG laser (532 nm) was used to ablate the soil samples in air at atmospheric pressure. The optical emission spectra demonstrate the presence of the spectral lines of Si, Fe, Al, Ca, Ti, K, Cr, Mg, Na, Ba, and Li in all of the samples. The emission lines intensities, electron number densities, and excitation temperatures were significantly enhanced in the presence of an external 0.3 T magnetic field applied perpendicular to the plasma plume. A maximum enhancement factor of approximately 8 was observed in the emission intensity. The emergence of several additional lines has also been detected using the magnetic field-assisted LIBS approach. The elemental composition determined using calibration-free laser-induced breakdown spectroscopy (CF-LIBS), with and without magnetic field, reveals that the external magnetic field only adjusts the laser-generated plasma dynamics without affecting the quantitative analysis of the samples. Importantly, the toxic and heavy elements such as chromium and barium were detected and quantified in all of the soil samples by both of these techniques. The variations in the compositional analysis using CF-LIBS with and without the applied magnetic field and LA-TOF-MS were less than 10%.